Creation of Data Repositories to Advance Nursing Science. (January 2019) - Perazzo, Joseph; Rodriguez, Margaret; Currie, Jackson; Salata, Robert; Webel, Allison R.
Data repositories are a strategy in line with precision medicine and big data initiatives, and are an efficient way to maximize data utility and form collaborative research relationships. Nurse researchers are uniquely positioned to make a valuable contribution using this strategy. The purpose of this article is to present a review of the benefits and challenges associated with developing data repositories, and to describe the process we used to develop and maintain a data repository in HIV research. Systematic planning, data collection, synthesis, and data sharing have enabled us to conduct robust cross-sectional and longitudinal analyses with more than 200 people living with HIV. Our repository building has also led to collaboration and training, both in and out of our organization. We present a pragmatic and affordable way that nurse scientists can build and maintain a data repository, helping us continue to make to our understanding of health phenomena.